2017
DOI: 10.1111/jam.13523
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal cooperation of phytochemicals and micronutrients against typical and atypical forms ofBorreliasp.

Abstract: Presented here in vitro results might help advancing our knowledge and improving the approach to target Borrelia sp.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 71 publications
0
6
0
Order By: Relevance
“…Previously we reported that particular phytochemicals such as polyphenols (baicalein, luteolin, and rosmarinic acid), fatty acids (monolaurin, 10-CDA), and iodine express in vitro antibacterial efficacy when applied individually and in dual combinations against the Borrelia spp. that are recognized as causative pathogens of LD in the USA and Europe [32,39]. In the present in vitro study we took another step towards increasing the efficacy and expanding the pleotropic mechanistic effects of these selected compounds against Borrelia spp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously we reported that particular phytochemicals such as polyphenols (baicalein, luteolin, and rosmarinic acid), fatty acids (monolaurin, 10-CDA), and iodine express in vitro antibacterial efficacy when applied individually and in dual combinations against the Borrelia spp. that are recognized as causative pathogens of LD in the USA and Europe [32,39]. In the present in vitro study we took another step towards increasing the efficacy and expanding the pleotropic mechanistic effects of these selected compounds against Borrelia spp.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we showed that the combinations of baicalein with luteolin as well as monolaurin with cis-2-decenoic acid displayed synergistic anti-spirochete and additive anti-biofilm effects. Moreover, baicalein and luteolin when combined with rosmarinic acid or iodine produced additive bacteriostatic and bactericidal effects against spirochetes and persisters, respectively [39].…”
Section: Introductionmentioning
confidence: 99%
“…Rosmarinic acid is an active component of the Lamiaceae (Labiatae) family and has been associated with anti-inflammatory and antioxidant activity [ 159 ]. According to Goc and colleagues [ 160 ], the addition of rosmarinic acid in conjunction with either luteolin or baicalein had additive bacteriostatic effects on B. burgdorferi anti-spirochetal activity.…”
Section: Discussionmentioning
confidence: 99%
“…In their 2021 paper, Zhang and colleagues [ 74 ] provided evidence that baicalein showed good in vitro activity against B. duncani , superior to both quinine and clindamycin. Interestingly, Goc and colleagues [ 160 ] have been able to show synergistic outcomes when baicalein was combined with other nutraceuticals, such as luteolin. This combination showed synergistic cooperation in killing knob-/round-shaped persistent forms and additive effects in the eradication of biofilms formed by the Borrelia burgdorferi and B. garinii studied.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the effects of several phytochemicals on Borrelia have been studied and found to be effective against the different pleomorphic forms of the bacteria [8][9][10][16][17][18]. For instance, Stevia whole leaf extract has been found to reduce the size and number of Borrelia biofilms [10].…”
Section: Discussionmentioning
confidence: 99%